KLASIFIKASI KENDALA GURU SEKOLAH DASAR DALAM PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI - Aisyah Iswala; Shevia Angel Widawati; Alyaa Nuur Fariidah; Qeynaya Zahra Adira Putri; Luna Jelita; Delia Indrawati; Hana Andriningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and classify the obstacles faced by elementary school teachers in utilizing technology-based learning media. The research method used is a Systematic Literature Review (SLR) with a qualitative descriptive approach. Data were obtained from 20 relevant journal articles published between 2021–2026. The results show that technology-based learning media have significant potential to improve the quality of learning, particularly in enhancing student engagement and understanding. However, several obstacles were identified, including: (1) teacher competence, (2) facilities and infrastructure, (3) access to technology and internet, (4) training and institutional support, and (5) pedagogical challenges. These obstacles are interconnected and influence the effectiveness of technology integration in learning. Therefore, a comprehensive and integrated approach is required to optimize the use of technology in elementary education.